Toward an Ecology of Learning from Experience: A Model for Further Research - Nancy Lloyn Pfahl (Adult Education Research Conference, 2007)
This emergent learning model derived from a narrative inquiry into epistemological processes governing institutional transformation. Our collaborative learning journey unfolded as a collection of organizational learning tales told by a team of nine college leaders. This paper and model describe the form of collective learning that preceded each systemic change.